Association of myocardial iron deficiency based on T2* CMR with the risk of mild left ventricular dysfunction in HIV-1-infected patients - Yan, Chengxi; Li, Ruili; Zhang, Jiannan; Zhang, Li; Yang, Minglei; Zhang, Qiujuan; Li, Hongjun (Frontiers in Cardiovascular Medicine, 2023)
Objectives —— This study sought to noninvasively determine myocardial iron levels in HIV-1-infected patients using CMR and explore the association between T2* values and mild left ventricular systolic dysfunction (LVSD). Methods —— This prospective study was conducted from June 2019 to July 2021. HIV-1-infected adults and healthy controls were consecutively enrolled for CMR exam. CMR exam included the assessment of myocardium iron content (T2*), cardiac function (cine), inflammation (T2), and fibrosis (through extracellular volume fraction [ECV] and late gadolinium enhancement [LGE]) measurements. Mild LVSD is defined as a left ventricular ejection fraction (LVEF) between 40% and 49%. Results ——Of 47 HIV-1-infected patients enrolled, 12 were diagnosed with mild LVSD (HIV-1+/LEVF+) and 35 were diagnosed with preserved LV function (HIV-1+/LEVF-). Compared with healthy controls, HIV-1-infected patients displayed higher T2*, T1, T2, ECV values and lower global circumferential strain (GCS) and global radial strain (GRS) (all P<0.05). However, between patients with and without mild LVSD, only the T2* values and ECV (all P <0.05) were different. The association between increased T2* values (>26 ms) and mild LVSD remained significant after adjusting for the established univariate predictors (ECV >32.9%, T1 values >1336 ms) of mild LVSD (odds ratio [OR], 10.153; 95% confidence interval [CI] 1.565-65.878, P=0.015). Conclusions ——Myocardial T2* values were elevated in HIV-1-infected patients, supporting the notion that ID was associated with mild LVSD. Our findings highlight the potential for ID in HIV-1-infected patients as an auxiliary biomarker to monitor the course of LVSD.